The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1002/ece3.3994
|View full text |Cite
|
Sign up to set email alerts
|

Bioclimatic and altitudinal variables influence the potential distribution of canine parvovirus type 2 worldwide

Abstract: Canine parvovirus type 2 (CPV‐2) is extremely contagious and causes high rate of morbidity to many wild carnivores. It has three variants (CPV‐2a, CPV‐2b, and CPV‐2c) that are distributed worldwide with different frequencies and levels of genetic and antigenic variability. The disease poses a threat to the healthy survival and reproduction of wildlife. The research on the relationship between CPV‐2 epidemic and environmental variables is lacking. To fill this research gap, we used maximum entropy (MaxEnt) appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…In our study, the median age was 4 months old and young age (<2 years old), and this age group was significantly associated with an increased risk of being hospitalized at the BICU with parvovirosis. These results are consistent with the known epidemiological factors of parvovirosis which mainly affects puppies aged between 6 weeks and 6 months [ 8 , 24 , 30 , 35 , 36 ]. Some previous studies also found more cases and increased mortality among male patients [ 36 , 37 ], especially in intact males older than 6 months [ 8 , 24 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, the median age was 4 months old and young age (<2 years old), and this age group was significantly associated with an increased risk of being hospitalized at the BICU with parvovirosis. These results are consistent with the known epidemiological factors of parvovirosis which mainly affects puppies aged between 6 weeks and 6 months [ 8 , 24 , 30 , 35 , 36 ]. Some previous studies also found more cases and increased mortality among male patients [ 36 , 37 ], especially in intact males older than 6 months [ 8 , 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…This might be explained by a temperate climate of the Lisbon area, which records an average temperature of 8 °C–15 °C in winter and 18 °C–28 °C in the summer [ 34 ]. A peak incidence of parvovirosis during summer months described in some studies is associated with an increasing rate of outdoor activities by dogs, increasing the chance of viral exposure [ 8 , 24 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The downloaded layer format of environment variables also needed to be converted to the ASCII format required by the Maxent software. As too many environmental variables would increase the complexity of the model and the random error and reduce the accuracy of the prediction results, the SPSS22 (Statistical Product and Service Solutions) software was used to perform principal component analysis (PCA) and correlation analysis on the attribute values of 68 environmental variables of the three species (Jiang, 2018). Among the 67 climatic variables we selected, 19 bioclimatic and 48 other monthly related climatic variables have great similarities.…”
Section: Environmental Variables and Processingmentioning
confidence: 99%
“…Initially, 29 bioclimatic/environmental variables that may affect the species distribution were considered. They include growing season-length TREELIM (Gsl, number of days), The mean temperature of the growing season TREELIM (Gst, °C), Near-surface relative humidity (Hurs, %), Potential evapotranspiration (Pet, kg m −2 month −1 ), Near-surface wind speed (Sfcwind, m s −1 ), Accumulated precipitation amount on (Gsp, kg m −2 gsl −1 ), Climate moisture index (CMI, kg m −2 month −1 ), Annual mean temperature (Bio1, °C), Mean Diurnal Range (Mean of monthly (max temp–min temp) (Bio2, °C), Isothermality (BIO2/BIO7) (× 100) (Bio3, °C), Temperature Seasonality (standard deviation × 100) (Bio4, °C), Max Temperature of Warmest Month (Bio5, °C), Min Temperature of Coldest Month (Bio6, °C), Temperature Annual Range (BIO5-BIO6) (Bio7, °C), Mean Temperature of Wettest Quarter (Bio8, °C ), Mean Temperature of Driest Quarter (Bio9, °C), Mean Temperature of Warmest Quarter (Bio10, °C), Mean Temperature of Coldest Quarter (Bio11, °C), Max Temperature of Warmest Month (Bio12, °C), Precipitation of Wettest Month (Bio13, mm), Precipitation of Driest Month (Bio14, mm), Precipitation Seasonality (Coefficient of Variation) (Bio15, mm), Precipitation of Wettest Quarter (Bio16, mm), Precipitation of Driest Quarter (Bio17, mm), Precipitation of Warmest Quarter (Bio18, mm), Precipitation of Coldest Quarter (Bio19, mm) 29 – 31 following with Slope (%) and Solar-radiation Aspect Index, derived from The SRTM (Shuttle Radar Topography Mission data) aimed to prepare the digital elevation model (DEM) 27 , 32 , 33 .…”
Section: Methodsmentioning
confidence: 99%